TOTAL PHENOLS, ANTIOXIDANT ACTIVITY AND YIELD, IN TOMATOES AND PEPPERS IN A CLOSED GREENHOUSE AND COMPARISON WITH A CONVENTIONAL GREENHOUSE - GOUGOULIAS, Nikolaos; PAPACHATZIS, Alexandros; VAGELAS, Ioannis; GIURGIULESCU, Liviu; KARABOULA, Anastasia; KALFOUNTZOS, Dimitrios (Studia Universitatis Babeș-Bolyai Chemia, 2016)
A study during 36 months, was conducted in a conventional greenhouse (open type) and a geothermal greenhouse (closed type) of TEI Thessaly to determine the productivity, total phenols content, antioxidant activity and certain qualitative characteristics of hydroponic tomatoes and peppers. At geothermal greenhouse the concentration of total phenols in tomatoes ranged from 151 to 324.5 µg (GAE) /g fresh weight and the antioxidant activity ranged from 3.54 to 3.90 µM (AA) /g fresh weight, while in peppers the total phenols ranged from 597 to 815 µg (GAE) /g fresh weight and the antioxidant activity ranged from 6.3 to 7.2 µM (AA) /g fresh weight. At the conventional greenhouse, the concentration of total phenols in tomatoes ranged from 163 to 195 µg (GAE) /g fresh weight and the antioxidant activity ranged from 3.3 to 3.9 µM (AA) /g fresh weight, while in peppers the total phenols ranged from 527 to 729 µg (GAE) /g fresh weight and the antioxidant activity ranged from 5.7 to 6.8 µM (AA) /g fresh weight. In tomatoes the yield of the production was higher in the geothermal greenhouse as compared to the conventional greenhouse, while in peppers the yield of the production between of geothermal greenhouse and of conventional greenhouse showed no statistically significant differences.